Executive Committee Minutes 2014-05-01 - Academic Senate:::::::::
Agenda approved. Minutes of 4/3 and 4/17 approved. Chair Report. Request for Posthumous Degree for Ivan Tapia-Solis approved for the Senate consent calendar. Quorum for Summer Ex Com determined. Provost Report. Statewide Senator Report. S&F proposal regarding APC for AY '14 – '15 – approved and additional on this topic motion also approved. EPC Report. Revision the Student Grievance Policy approved for the Senate agenda. FSAC Report. Vice Chair Report. Resolution on Improving SSU Services to Service Members and their Families approved for the Senate agenda. Questions for Vice President of Administration and Finance. Vice President of Student Affairs Report. CFA Report. Associated Students Report. Senate agenda approved.